Pengembangan Media IV-GLOW untuk Meningkatkan Motivasi Belajar Pemanasan Global Peserta Didik SMA di Kabupaten Jombang - Ilmi, Rosikhotul; Anggaryani, Mita (Universitas Negeri Surabaya, 2024)
Technology is increasingly developing and becoming a support in the field of education, one of which is in the development of learning media. The development of increasingly superior learning media can support the delivery of material to students. Learning media is divided into several types, one of which is audio-visual learning media in the form of interactive learning videos. Interactive learning is able to provide a more effective learning experience because it combines several senses, so that students will find it easier to remember the learning material. This research aims to develop interactive video learning media on global warming materials. In this study, the next learning media called Interactive Video of Global Warming (IV-GLOW) was piloted to increase students' learning motivation. This research uses the Research and Development method. Data is collected through validation and questionnaires. The results of this study show that IV-GLOW media has a validity percentage of 97.78% with very valid criteria. The practicality of IV-GLOW media obtained an average percentage of 90.53%. In its implementation, IV-GLOW media can be used .The increase in motivation occurs in all aspects with the highest increase in relevance and satisfaction indicators.